Project-Based Learning Implementation in Higher Education for Econometrics Science - Vidya Purnamasari; Vika Annisa Qurrata; Sugeng Hadi Utomo; Tamat Sarmidi (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
Econometrics is an essential science in Development Economics because it can improve students' ability to process data and analyze economics. Monotonous lecture activities and student difficulties in lectures are associated with theories taught in real situations. One way to improve student's practical abilities is through innovative learning models. Learning innovations make students learn to be active in expressing discussions about current economic issues supported by analytical skills in the field, which will increase student enthusiasm. Through Project-based Learning (PjBL), students have to follow the learning process actively. Lecturers will be the leader to the process in order to giving the feedback and assess the learning process. This model enhances students' ability to solve problems directly and then solve them by engaging project work directly and enabling them to act and think creatively, improve collaborative skills, and increase enthusiasm. Using a quasi-experimental, the study involving a sample of 59 people taken by a simple random sampling technique. The data collected were analyzed using a one-time ANOVA test. The application of this model is carried out online and packaged by applying various combinations of technologies. Empirical evidence shows simultaneously significant differences in learning outcomes and problem-solving abilities in undergraduate students using the PjBL method compared to conventional methods. This study concludes that the PjBL model effectively improves the ability to think actively and solve problems for students in the Econometrics course. The implementation results of this study can be the innovative technology-based learning methods that are attractive to undergraduate students in subjects that require high critical thinking skills.